Cortisol secretion predicts functional macro-scale connectivity of the visual cortex: A data-driven Multivoxel Pattern Analysis (MVPA). (July 2020) - Muehlhan, Markus; Alexander, Nina; Trautmann, Sebastian; Weckesser, Lisa J.; Vogel, Susanne; Kirschbaum, Clemens; Miller, Robert
Graphical abstract: Highlights: Data-driven identification of resting state connectivity seeds covarying with cortisol. Cortisol connects visual areas to large lateral clusters. Covered regions correspond to the salience-, control & motor-network. Dose-response association of cortisol levels and functional connectivity. Abstract: Background: Functional connectivity is a fundamental principle of brain organization. Cortisol, the end product of the hypothalamic–pituitary–adrenal axis, is a potent modulator of brain functions. Previous studies investigating the association between cortisol levels on brain connectivity are, however, limited to specific a priori defined brain networks. Such hypothesis-driven approaches only partly capture the full extent of spatial modulatory effects that cortisol exerts on brain connectivity. Consequently, the aim of this study was a data-driven identification of brain regions where connectivity patterns covary significantly with cortisol levels. Methods: Eighty-eight healthy right-handed individuals participated in a task-independent fMRI-resting-state functional connectivity (rsFC) measurement. The cortisol concentrations in saliva were measured at eight points in time around the resting state measurement. Using a multi-voxel pattern analysis (MVPA), seed regions were identified whose activity covaried strongest with cortisol levels. Seed-to-voxel analyses were then performed to isolate corresponding networks affected by cortisol variation. Results: The MVPA identified three regions in the primary and secondary visual cortex where connectivity patterns were associated with cortisol secretion. Seed-to-voxel analysis revealed large lateral connectivity clusters that mainly correspond to the salience and control network, but also to auditory and pericentral regions. Subsequent dose-response analysis suggests that cortisol levels below ∼10 nmol/L weakly influenced connectivity between the identified regions. Discussion: The results indicate a dose-dependent association between cortisol levels and the rsFC of the visual cortex to several lateral brain regions associated with perception, attention, cognition, salience mapping and motor actions. It is possible that the effects of cortisol on cognitive functions may be (at least partially) mediated by cortisol effects on the underlying sensory processes.